Responses of IgE, IgG1, and IgG4 to concanavalin A-binding Blomia tropicalis antigens in allergic patients - Almeida,K.C. (2006)
Blomia tropicalis (Bt) and Dermatophagoides pteronyssinus (Dp) are the prevalent house dust mites in tropical countries and are associated with allergic diseases. Glycosylated antigens are highly immunogenic and involved in different pathologies. We evaluated the presence of IgE, IgG1, and IgG4 to concanavalin A-binding antigens (Bt-Con-A) isolated from Bt-total extract in sera of allergic and non-allergic subjects. Bt-total and Bt-Con-A extracts were evaluated by SDS-PAGE and ELISA for reacting with IgE, IgG1, and IgG4 in sera of 121 patients with allergic rhinitis and 36 non-allergic individuals. All subjects were skin prick tested with Bt-total extract and inhibition tests were performed for IgE, IgG1, and IgG4 using both extracts (Bt-total and Bt-Con-A). Skin prick test showed that 58% of the patients were sensitized to Bt (Bt+), with 52% reactive to both mites (Bt and Dp) and 6% to Bt only. A broad spectrum of proteins (14-152 kDa) was visualized in Bt-total and components >27 kDa for the Bt-Con-A extract. ELISA showed a similar profile of IgE, IgG1 and IgG4 levels in response to Bt-total and Bt-Con-A extracts in different groups, although Bt+ patients showed a lower IgG4 reactivity to Bt-Con-A extract. Specific IgG1 levels were higher in Bt+ patients than in control subjects, and IgG4 levels showed no significant difference among groups. ELISA inhibition showed a partial IgE and total IgG1 and IgG4 cross-reactivity with Dp extract for Bt-total and Bt-Con-A extracts. We conclude that Con-A-binding components isolated from Bt constitute major allergens and are involved in both allergen sensitization (IgE response) and homeostasis maintenance (IgG1 and IgG4 responses).